2008
DOI: 10.1377/hlthaff.27.2.507
|View full text |Cite
|
Sign up to set email alerts
|

Disparities In Physician Care: Experiences And Perceptions Of A Multi-Ethnic America

Abstract: This 2007 Harvard School of Public Health/Robert Wood Johnson Foundation survey of 4,334 randomly selected U.S. adults compared perceptions of the quality of physician care among fourteen racial and ethnic groups with those of whites. On each measure examined, at least five and as many as eleven subgroups perceived their care to be significantly worse than care for whites. In many instances, subgroups were at least fifteen percentage points more negative than whites. This was true for Central/South Americans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 8 publications
3
38
0
Order By: Relevance
“…In a 2007 survey of 4,334 randomly selected US adults, age 18+ years, Blendon et al 13 compared perceptions of the quality of physician care among 14 racial and ethnic groups to those of nonHispanic Whites. With the exception of American Indians (N = 102), each pan-racial group contained slightly more than 1,000 respondents.…”
Section: Diverse Healthcare Experiences In a Diverse Americamentioning
confidence: 99%
“…In a 2007 survey of 4,334 randomly selected US adults, age 18+ years, Blendon et al 13 compared perceptions of the quality of physician care among 14 racial and ethnic groups to those of nonHispanic Whites. With the exception of American Indians (N = 102), each pan-racial group contained slightly more than 1,000 respondents.…”
Section: Diverse Healthcare Experiences In a Diverse Americamentioning
confidence: 99%
“…In addition, social stress theory affirms that disenfranchised populations might experience increased stress because of the inequalities found in the social organization in which the individual or family is embedded (Aneshensel). This is particularly relevant for ethnic minority groups, including Hispanics, because of the significant health disparities (Agency for Healthcare Research and Quality, 2009;Szapocznik, Prado, Burlew, Williams, & Santisteban, 2007) and structural exclusion (Blendon et al, 2008;Snowden, 2005) experienced by this segment of the population. Stressful life experiences can cause negative emotional and biological reactions that impact mental and physical health (Cohen, Kessler, & Underwood, 1995).…”
Section: Social Stress and Minority Statusmentioning
confidence: 99%
“…Language proficiency, insurance availability, time away from work, and low income combined with out-of-pocket expenses, and even lack of citizenship, are some of the barriers experienced by minorities that prevent them from having a usual source of care, thus leading to health disparities and poorer overall health 1 14 15…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…Having health insurance decreases health disparities among high and low SES groups by facilitating access to preventive and primary care while lowering the overall cost 13 15 16. Although many uninsured minorities are eligible for insurance, they often do not sign up for it due to lack of awareness or limited proficiency in English,11 although a Californian study showed high (88%) English proficiency among NHPI 1…”
Section: Global Health Problem Analysismentioning
confidence: 99%